1999
DOI: 10.1128/jvi.73.9.7381-7389.1999
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Antigen Presentation by the Glycine/Alanine Repeat Domain Is Not Conserved in Simian Homologues of Epstein-Barr Virus Nuclear Antigen 1

Abstract: Most humans and Old World nonhuman primates are infected for life with Epstein-Barr virus (EBV) or closely related gammaherpesviruses in the same lymphocryptovirus (LCV) subgroup. Several potential strategies for immune evasion and persistence have been proposed based on studies of EBV infection in humans, but it has been difficult to test their actual contribution experimentally. Interest has focused on the EBV nuclear antigen 1 (EBNA1) because of its essential role in the maintenance and replication of the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1

Year Published

2001
2001
2009
2009

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(15 citation statements)
references
References 38 publications
2
12
1
Order By: Relevance
“…Although one may argue that the Rh-EBNA1 protein is differentially processed in human and primate cells, data presented in this study clearly show that both human and simian cells efficiently process CTL epitopes from Rh-EBNA1. These observations are also supported by earlier studies of Blake and colleagues, who showed that rhesus B cells and fibroblasts expressing Rh-EBNA1 containing a model CTL epitope from the simian immunodeficient virus are efficiently recognized by virus-specific CTL [13]. Furthermore, the impairment of translation and endogenous processing of Rh-EBNA1 following substitution of its native GAr domain with GAr sequences from Hu-EBNA1 highlights the impact of varying GAr sequences on the self-synthesis of EBNA1 homologues.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…Although one may argue that the Rh-EBNA1 protein is differentially processed in human and primate cells, data presented in this study clearly show that both human and simian cells efficiently process CTL epitopes from Rh-EBNA1. These observations are also supported by earlier studies of Blake and colleagues, who showed that rhesus B cells and fibroblasts expressing Rh-EBNA1 containing a model CTL epitope from the simian immunodeficient virus are efficiently recognized by virus-specific CTL [13]. Furthermore, the impairment of translation and endogenous processing of Rh-EBNA1 following substitution of its native GAr domain with GAr sequences from Hu-EBNA1 highlights the impact of varying GAr sequences on the self-synthesis of EBNA1 homologues.…”
Section: Discussionsupporting
confidence: 79%
“…However, extensive analysis of rhesus LCV EBNA1-specific CTL expanded from LCV-infected animals revealed that these effector cells fail to recognize full-length EBNA1 protein, while a sequence in which internal repeats were deleted was efficiently recognized [12]. These observations contradict the previous studies by Blake and colleagues who showed that in contrast to EBV EBNA1, the internal repeat sequences within rhesus EBNA1 do not inhibit endogenous processing of CTL epitopes from this protein [13]. These contrasting observations raise important questions regarding the overall biology of LCV infection and the mechanism by which the strongly dominant EBNA1-specific CD8 + T cell responses can be generated in LCV-infected animals.…”
Section: Introductioncontrasting
confidence: 67%
See 2 more Smart Citations
“…Vaccinia viruses expressing HLA alleles B*3501 and B*2704 have been described previously. 20,21 Recombinant viruses expressing A*2501 and B*4402 were constructed using standard procedures. 22 Vaccinia infections were performed at a multiplicity of infection of 10 for 1 hr at 37u.…”
Section: Recombinant Vaccinia Virusesmentioning
confidence: 99%